Physical Burden among Caregiver of Child with Nephrotic Syndrome in Najaf City in Iraq - Entesar Abdulameer Fajr (Indian Journal of Forensic Medicine & Toxicology, 2021)
Caregiver of children with Nephrotic syndrome report negative impact on their physical and psychological health. The descriptive (cross-sectional) research is an investigation done to determine the physical burden among caregivers of children with Nephrotic syndrome. During the time from September 23, 2018 to September 1, 2019, an intended (non-random) samples (115) are select from Al-Sadr Medical City in Najaf city. The tool is present to (21) professionals from different academies to be effective, and the reliable of the tool is determine complete by coefficient alpha implicit, and the consistency of this tool is (r = 0.81). Nephrotic syndrome is the greatest cause of burden for patients and caregiver. This may be related to patients, needs that include physical, psychological, and emotional support. This requires much knowledge and more skills from caregivers and developed responsibilities for them. These responsibilities may lead to much burden that includes social and economic burdens. It can be concluded that more than half of the caregiver of child with Nephrotic Syndrome were affect by physical burden at moderate to severe degree.